Kemijska sestava in potencialna uporabnost lignoceluloznih ostankov - Zule, Janja (Acta silvae et ligni, 2022)
The main purpose of the current research was to determine the chemical structure of typical lignocellulosic residues generated in wood processing industries, fruit and vine growing activities, and the maintenance of green areas. Four characteristic groups of samples, e.g. wood sawdust, bark, tree prunings and the lignified residues of fruits were analysed for the content of ash, lipophilic and hydrophilic extractives, cellulose, hemicellulose and lignin. Gravimetric methods were used for the analyses, and the purity of individual isolated fractions was monitored by FTIR spectroscopy. The highest quantity of ash and low molecular weight extractive compounds was determined in bark and tree prunings, while concentrations of cellulose and total carbohydrates were highest in sawdust samples. Lignified fruit residues and bark proved to be rich sources of lignin. Because of their diverse chemical composition, all of the examined materials are potential feedstocks for the production of platform chemicals and other specific products within biorefinery processes.
Keywords: bark; biorafinerije; biorefineries; chemical composition; fruit residues; innovative products; inovativni produkti; kemijska sestava; lignocellulosic residues; lignocelulozni ostanki; ostanki sadežev; sawdust; skorja; tree prunings; zeleni odrez; žagovina